(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Despite being two of the most significant mental disorders, limited research has been conducted to investigate childhood antecedents of anxiety and depression in adults outside of traumatic events. Parenting styles and peer relationship factors have been implicated in childhood psychopathology. This study sought to find associations between college students’ current anxiety and/or depression symptomatology, and their retrospective reports of childhood parenting style factors and peer relationships. Participants (N = 206) were recruited through a local University and all questionnaires were completed online. Correlational analysis revealed significant associations between current depression symptoms and childhood bullying and victimization. Also, anxiety symptoms were associated with victimization. MANOVA results revealed significant differences between mother’s over control, indifference, and abuse with current depression and anxiety scores. Father’s abuse was also associated with current depression. This research shows that effects from important early relationships can be long lasting, and highlights the need for appropriate interventions.